2021
DOI: 10.1088/2053-1591/ac1003
|View full text |Cite
|
Sign up to set email alerts
|

Silver decorated lanthanum calcium manganate for electrochemical supercapacitor

Abstract: Perovskite La0.5Ca0.5MnO3 (LCM) based materials are promising for electrode construction but their poor conductivities often lead to limited electrochemical performances. In this work, LCM was combined with Ag through the two-step process based on sol-gel and silver mirror reaction. The as-obtained LCM@Ag composites were characterized by scanning electron microscopy and x-ray powder diffraction. The mass percent determined by energy disperse spectroscopy combined with x-ray photoelectron spectroscopy was estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Figure 3a-d show the Mn 2p spectra, while Figure 3e-h show the O 1s spectra of the Mn AGL, Mn AGL @200, Mn AGL @400, and Mn AGL @550 AGL samples. These spectra contained one spin-orbit peak, at ~642 eV for Mn 2p 3/2 and ~654 eV for Mn 2p 3/2 ; these were deconvoluted by fitting along with the typical satellite peaks of Mn [34]. The spin-orbit splitting, denoted by the difference in the binding energy values of the two levels, was 12 eV, which was consistent with that reported for Mn-based systems [35].…”
Section: Resultssupporting
confidence: 83%
“…Figure 3a-d show the Mn 2p spectra, while Figure 3e-h show the O 1s spectra of the Mn AGL, Mn AGL @200, Mn AGL @400, and Mn AGL @550 AGL samples. These spectra contained one spin-orbit peak, at ~642 eV for Mn 2p 3/2 and ~654 eV for Mn 2p 3/2 ; these were deconvoluted by fitting along with the typical satellite peaks of Mn [34]. The spin-orbit splitting, denoted by the difference in the binding energy values of the two levels, was 12 eV, which was consistent with that reported for Mn-based systems [35].…”
Section: Resultssupporting
confidence: 83%
“…The key to the improved performance can be attributed to the introduction of silver nanoparticles that enhanced the electron transport and ion diffusion capabilities of the composites. 153 154 The double perovskite structure has a more ordered structural arrangement than element-doped perovskites, which can prevent lattice distortion and improve cyclic stability. Tomar et al revealed that the B-site cation ordering in the double perovskite Sr 2 CoMoO 6Àd (DP-SCM) tends to favor the rock salt structure (0D arrangement).…”
Section: Abo 3 Type Perovskite Fluoridementioning
confidence: 99%
“…The key to the improved performance can be attributed to the introduction of silver nanoparticles that enhanced the electron transport and ion diffusion capabilities of the composites. 153 Tian et al constructed LaMnO 3 @NiCo 2 O 4 materials with layered nanosheet morphology on nickel foam for SCs. The encapsulation of LaMnO 3 nanoparticles in NiCo 2 O 4 nanosheets effectively suppressed the leaching of Mn species during reversible intercalation and significantly improved the electrical conductivity.…”
Section: All-inorganic Perovskite For Supercapacitorsmentioning
confidence: 99%
“…Therefore, LaMnO 3 has been widely studied as an electrode material for supercapacitors. [19][20][21][22][23] In recent years, research on lanthanide-based perovskite oxides has revealed that the concentration of carriers and oxygen vacancies can be regulated by partial substitution of cations at A-or B-site, thus effectively enhancing the electrochemical performance of the materials. [24][25][26][27][28][29][30][31] Based on the charge storage mechanism, the high specific capacitance of perovskite materials is mainly attributed to the pseudocapacitance generated by oxygen anion-intercalation.…”
Section: Introductionmentioning
confidence: 99%
“…LaMnO 3 perovskite is a typical ABO 3 ‐type structure due to its ability to store charges in vacant sites (oxygen and cations) through intercalation and reversible Faraday surface reactions. Therefore, LaMnO 3 has been widely studied as an electrode material for supercapacitors [19–23] . In recent years, research on lanthanide‐based perovskite oxides has revealed that the concentration of carriers and oxygen vacancies can be regulated by partial substitution of cations at A‐ or B‐site, thus effectively enhancing the electrochemical performance of the materials [24–31] .…”
Section: Introductionmentioning
confidence: 99%